Pengaruh Pemberian N 2,4-D Terhadap Pertumbuhan dan Metabolisme Kalus Kedelai Pada Kondisi Hipoksida Secara Invitro - Elita Kumianjani A B; Revandi iskandar Damanik; Luthfi A. M. Siregar (Jurnal Agroekoteknologi, 2016)
Soybean demand continues to increase as the number of people , but the production has not be enable to meet the needs of national soybean. One effort to increase production is to indentificat soybean acreage of inundation. The aims of the research was to determine about Identification callus of soybean toward inundation by in vitro. This research was carried out in The Tissue Culture Laboratory, Agriculture’s Faculty Of North Sumatera University from August to March 2015. Completely Randomized Design with two factors was used, first factor was auxin 2,4-D concentration consist of three leevels : 0 ppm; 2 ppm; 4 ppm. The second factor was Inundation and without Inundation. The parameters measured were are visualization of callus, percentage of growth callus, percentage of weight callus , the amount of chlorophyll a and b, and concentration of protein. The results showed that 2,4-D concentration and Inundation give significant effect on visualization of callus, percentage of growth callus, percentage of weight callus , the amount of chlorophyll a and b, and concentration of protein , but it have no significantly effect on the formation of chlorophyll a in the phase of inundation and interactions between as given significantly effect on all parameters.Keywords : 2,4-D, Hipoksida, In vitroSoybean demand continues to increase as the number of people , but the production has not be enable to meet the needs of national soybean. One effort to increase production is to indentificat soybean acreage of inundation. The aims of the research was to determine about Identification callus of soybean toward inundation by in vitro. This research was carried out in The Tissue Culture Laboratory, Agriculture’s Faculty Of North Sumatera University from August to March 2015. Completely Randomized Design with two factors was used, first factor was auxin 2,4-D concentration consist of three leevels : 0 ppm; 2 ppm; 4 ppm. The second factor was Inundation and without Inundation. The parameters measured were are visualization of callus, percentage of growth callus, percentage of weight callus , the amount of chlorophyll a and b, and concentration of protein. The results showed that 2,4-D concentration and Inundation give significant effect on visualization of callus, percentage of growth callus, percentage of weight callus , the amount of chlorophyll a and b, and concentration of protein , but it have no significantly effect on the formation of chlorophyll a in the phase of inundation and interactions between as given significantly effect on all parameters.Keywords : 2,4-D, Hipoksida, In vitro